Stereochemistry of metal tetramethylcyclam complexes directed by an unexpected anion effect. Issue 39 (26th May 2017) - Derrick, Jeffrey S.; Kim, Yujeong; Tak, Hyeonwoo; Park, Kiyoung; Cho, Jaeheung; Kim, Sun Hee; Lim, Mi Hee
Abstract : An unexpected anion effect leads to the direct and selective preparation of the trans -III-[Cu(TMC)] 2+ complex that is fully characterized by X-ray crystallography, UV-visible spectroscopy, advanced EPR spectroscopy, and computational studies. Abstract : Metal(TMC) complexes (TMC = tetramethylcyclam) exclusively form trans -I diastereoisomers; thus, little is known about the trans -III isomers. Herein, we report a new method to prepare the trans -III-[Cu(TMC)] 2+ complex via an anion effect. Our crystallographic, spectroscopic, and computational analyses validated that [Cu(TMC)](NO3 )2 produced the trans -III complex, different from the trans -I structure of [Cu(TMC)](ClO4 )2 .